Detecting Schistosoma infections in endemic countries: a diagnostic accuracy study in rural Madagascar - Eva Lorenz; Ravo Razafindrakoto; Pia Rausche; Zaraniaina Tahiry Rasolojaona; Nantenaina Matthieu Razafindralava; Alexandre Zerbo; Yannick Höppner; Heidrun von Thien; Njary Rakotozandrindrainy; Cheick Oumar Doumbia; Philipp Klein; Jean-Marc Kutz; et al. (Infectious Diseases of Poverty)
Abstract Background Schistosoma haematobium and S. mansoni are endemic in Madagascar, but reliable diagnostic tools are often lacking, contributing to exacerbate transmission and morbidity. This study evaluated the diagnostic accuracy of three tests for schistosome infection in Malagasy adults from areas of medium to high endemicity. Methods This cross-sectional study enrolled adults from three primary health care centres in Madagascar. Urine and blood samples were tested for schistosome infection using polymerase chain reaction (PCR), up-converting reporter particle lateral flow for the circulating anodic antigen (UCP-LF CAA), and point-of-care circulating cathodic antigen (POC-CCA) tests. Bayesian latent class models were used to assess diagnostic accuracies and disease prevalence. Results Of 1339 participants, 461 were from S. haematobium and 878 from S. mansoni endemic areas. Test detection rates were 52% (POC-CCA), 60% (UCP-LF CAA), and 66% (PCR) in the S. haematobium area, and 54%, 55%, and 59% respectively in the S. mansoni area. For S. haematobium, PCR and UCP-LF CAA showed high sensitivity (Se, median 95.2% and 87.8%) but moderate specificity (Sp, 60.3% and 66.2%), while POC-CCA performed moderately (Se: 64.5%; Sp: 59.6%). For S. mansoni, PCR and POC-CCA demonstrated high diagnostic accuracy (Se > 90%, Sp > 80%), while UCP-LF CAA showed good sensitivity (79.9%) but moderate specificity (69.7%). Conclusions While population-level prevalence estimates were similar across tests, individual-level agreement was only low to moderate. Our findings suggest that optimal diagnostic strategies should be tailored to specific endemic settings, continued development of accurate diagnostics suitable for highly endemic settings remains a priority. Graphical Abstract